PERCEIVED SOCIAL SUPPORT AMONG ELDERLY INDIVIDUALS RESIDING IN URBAN BENGALURU: A CROSS-SECTIONAL STUDY - H S, MOUNA; Lokanath, Hamsa; T Sobagaiah, Ranganath; Neela, Vishwanatha (International Journal of Medical Research and Review, 2023)
Introduction Increase in life expectancy results in an increasing elderly population which contributes to 9.3% of global population. With epidemiological transition of diseases, the burden of chronic morbidity conditions will also increase with an effect on Quality of life, which demands social support especially among elderly individuals. Hence the present study was taken up to assess social support among elderly individuals residing in urban field practice area of Bangalore Medical College & Research Institute (BMCRI), Bengaluru. Objective: To assess the perceived social support among elderly population residing in the urban field practice area of BMCRI Methodology: A cross sectional study was conducted to assess the perceived social support among 100 elderly population residing in the urban field practice area of BMCRI. Simple random sampling technique was used. Data was collected using validated Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire along with socio-demographic factors. Results: In this study, the mean age of the elderly individuals was 67.0 + 5.90 years, total social support score was 59.2 + 17.97. Perceived social support was found to be statistically significant found between characteristics gender, educational status, marital status, earning status, marital status, earning status, support obtained for medication and previous hospitalization. (p<0.05)